Does the position of a sustentacular screw influence the stability of a plate osteosynthesis of a calcaneal fracture? A biomechanical study. (September 2021) - Pazour, Jan; Horák, Zdeněk; Džupa, Valér
The purpose of the study was to compare the stability of the plate osteosyntheses of intra-articular calcaneal fractures using various types of a sustentacular screw insertions. A geometrical model of a calcaneal fracture was created. The fracture was fixed with a plate and screws with a uniform distribution. The individual models differed regarding the position of the sustentacular screw. The screw was inserted using three different variants: Model A: into the tip of sustentaculum tali, Model B: under the sustentaculum tali, and Model C: into the inferior peripherial rim of the sustentacular fragment. In all three variants, the screw was either locked into the plate via threads or unlocked. The model was loaded with force in the vertical direction. The stiffness of individual models was evaluated using the finite element method, which was expressed as the maximum force (Fmax ) that the system was able to transmit and by determining the magnitude and distribution of reduced stress (σred ) on the individual parts of the model of a fixed calcaneal fracture. The greatest stiffness of the system was observed in the Model B (Fmax  = 335.8 N). The least stiffness was observed in Model C (Fmax  = 296.3 N). This model also produced the greatest load on bone tissue was observed (σ max red  = 67.5 MPa). The least load on bone tissue was measured in Model B (σ max red  = 53.7 MPa). The load on the plate was similar in all three models (814.0–820.0 MPa). The analyses suggest that in a plate osteosynthesis of a calcaneal fracture, the insertion of a sustentacular screw under the tip of the sustentaculum tali is acceptable in terms of osteosynthesis stability. This sustentacular screw position reduces the risk of the screw penetrating into the talocalcaneal joint.